Population pharmacokinetic model for once‐daily intravenous busulfan in pediatric subjects describing time‐associated clearance. (16th June 2022) - Lawson, Rachael; Staatz, Christine E.; Fraser, Christopher J.; Ramachandran, Shanti; Teague, Lochie; Mitchell, Richard; O'Brien, Tracey; Hennig, Stefanie
Abstract: This study aimed to characterize the population pharmacokinetics (PK) of busulfan focusing on how busulfan clearance (CL) changes over time during once‐daily administration and assess different methods for measuring busulfan exposure and the ability to achieve target cumulative exposure under different dosing adjustment scenarios in pediatric stem cell transplantation recipients. Daily serial blood sampling was performed and concentration‐time data were analyzed using a nonlinear mixed‐effects approach. The developed PK model was used to assess achievement of target exposure under six dose‐adjustment scenarios based on simulations performed in RStudio (RxODE package)®. A total of 2491 busulfan plasma concentration–time measurements were collected from 95 patients characterizing 379 dosing days. A two‐compartment model with time‐associated CL best described the data with a typical CL of 14.5 L/h for an adult male with 62 kg normal fat mass (NFM; equivalent to 70 kg total body weight), typical volume of distribution central compartment (V1) of 40.6 L/59 kg NFM (equivalent to 70 kg total body weight), and typical volume of distribution peripheral compartment of 3.57 L/62 kg NFM. Model interindividual variability in CL and V1 was 14.7% and 34.9%, respectively, and interoccasional variability in CL was 6.6%. Patient size described by NFM, a maturation component, and time since start of treatment significantly influenced CL. Simulations demonstrated that using model‐based exposure estimates with each dose, and either a proportional dose‐adjustment calculation or model‐based calculated individual CL estimates to support dose adjustments, increased proportion of subjects attaining cumulative exposure within 5% of target compared with using noncompartmental analysis (100% vs. 0%). A time‐associated reduction in CL during once‐daily busulfan treatment was described.